Juridical Analysis of Cryptocurrency Transaction on The Binance Market in Terms of Commodity Futures Trading Regulatory Agency Regulations - Sumaryanto, A. Djoko; W.M, Wreda Danang; Razak, Abdul; Darmoko, Murry; Santoso, Bagus Teguh; Haryadi, Wahyu Tris (Acta Universitatis Danubius. Juridica, 2023)
The presence of Bitcoin as a digital currency whose management is handled by the developer as money might result in its restriction; consequently, the legality and legal ramifications of buying and selling Bitcoin, particularly on the Binance market, are still being determined. The goal of this research is to look at Regulation Number 5 of 2019 regarding technical provisions for holding a physical cryptocurrency market on commodity futures exchanges in the use of cryptocurrency on the Binance market, such as requirements for establishing a physical crypto asset market or trade, dispute resolution procedures, and legal protection.